Perioperative care of a patient with ovarian cancer - Porożyńska, Marcelina; Szablewska, Anna W. (Nursing Problems / Problemy Pielęgniarstwa, 2024)
Ovarian cancer is diagnosed most often in women already at an advanced stage. Symptoms are uncharacteristic and mainly involve gastrointestinal and urinary complaints. It causes the highest mortality rate among all female genital cancers. In 2020, 3131 deaths were caused by ovarian cancer itself. It occurs most often in peri- and postmenopausal women. However, observations indicate an increasing incidence of the disease among younger patients. Late diagnosis is an important problem, so women should be aware of potential risk factors and symptoms at an early age and make regular visits to a gynaecologist. The purpose of this paper is to present the clinical aspect of ovarian cancer and to emphasise the role of the midwife in the diagnostic and therapeutic process they play during the perioperative care of the patient. The nursing process was developed using the ICNP ® method.